2010
DOI: 10.1021/jm1005513
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mitogen-Activated Protein Kinase-Interacting Kinase 1 Inhibitors by a Comprehensive Fragment-Oriented Virtual Screening Approach

Abstract: Mitogen-activated protein kinase-interacting kinases 1 and 2 (MNK1 and MNK2) phosphorylate the oncogene eIF4E on serine 209. This phosphorylation has been reported to be required for its oncogenic activity. To investigate if pharmacological inhibition of MNK1 could be useful for the treatment of cancers, we pursued a comprehensive virtual screening approach to rapidly identify pharmacological tools for target validation and to find optimal starting points for a plausible medicinal chemistry project. A collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Closer investigation of the Mnk2D228G-staurosporine complex using docking methods showed that the rigid planar polycyclic ring system of staurosporine lies in a flat orientation in the ATP-binding pocket and the lactam ring forms a total of two hydrogen bonds with the Glu160 and Met162 residues in the hinge region [5]. Such an observation is consistent with the results obtained from a previous study, in which different docking methods were used to replicate the data [21]. Notably, the gatekeeper residue Phe159 in Mnk2 may assist in the formation of favorable hydrophobic interactions with the polycyclic ring system of staurosporine, possibly stabilizing the overall protein-ligand complex [3].…”
Section: Introductionsupporting
confidence: 89%
“…Closer investigation of the Mnk2D228G-staurosporine complex using docking methods showed that the rigid planar polycyclic ring system of staurosporine lies in a flat orientation in the ATP-binding pocket and the lactam ring forms a total of two hydrogen bonds with the Glu160 and Met162 residues in the hinge region [5]. Such an observation is consistent with the results obtained from a previous study, in which different docking methods were used to replicate the data [21]. Notably, the gatekeeper residue Phe159 in Mnk2 may assist in the formation of favorable hydrophobic interactions with the polycyclic ring system of staurosporine, possibly stabilizing the overall protein-ligand complex [3].…”
Section: Introductionsupporting
confidence: 89%
“…As shown in Figure , Cd‐induced ERK1/2 activation did not increase the level of p‐eIF4E. On the contrary, levels of p‐eIF4E and eIF4E in cells exposed to Cd were about half that of control cells without additional effect of LJI308 or ETP‐45835 which inhibits RSK and MNK1/2, respectively . Accordingly, none of these inhibitors modified the Cd‐induced increase in MTT‐reducing activity (Figure C).…”
Section: Resultsmentioning
confidence: 84%
“…Their catalytic domains share 78% sequence identity and the active sites are highly conserved [25,57]. MNK1 and MNK2 display the canonical bilobal arrangement of the ATP-binding cleft sandwiched in between the C-terminal and N-terminal lobes.…”
Section: Mapk-interacting Kinasesmentioning
confidence: 99%